1979
DOI: 10.1210/endo-105-3-708
|View full text |Cite
|
Sign up to set email alerts
|

19-Nor-Deoxycorticosterone: A Potent Mineralcocorticoid Isolated from the Urine of Rats with Regenerating Adrenals*

Abstract: Adrenal regeneration hypertension (ARH) is an experimental form of low renin hypertension in the rat in which an unknown mineralocorticoid (s) appears to contribute to the pathophysiology of the hypertension. To isolate unknown mineralocorticoids, urine of castrated rats with regenerating adrenals was lowered to pH 1.0 with sulfuric acid, incubated for 24-h at room temperature, extracted with ethyl acetate, and subjected to several successive chromatographic purifications. Unknown urinary mineralocorticoid act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…3 The identity of the hormone (or hormones) involved has not been clearly defined, although several steroids, including 11-deoxycorticosterone (DOC) and 19-nordeoxycorticosterone have been implicated. 4 " 7 Bergon and Brownie 8 found that serum DOC levels were elevated in adrenal-enucleated W/Fu 5 weeks after oper-ation as compared with those of controls. Again, BP was mildly elevated but cardiovascular lesions were absent.…”
mentioning
confidence: 99%
“…3 The identity of the hormone (or hormones) involved has not been clearly defined, although several steroids, including 11-deoxycorticosterone (DOC) and 19-nordeoxycorticosterone have been implicated. 4 " 7 Bergon and Brownie 8 found that serum DOC levels were elevated in adrenal-enucleated W/Fu 5 weeks after oper-ation as compared with those of controls. Again, BP was mildly elevated but cardiovascular lesions were absent.…”
mentioning
confidence: 99%
“…The radioimmunoassay for 19-nor-DOC has been previously described. 3 Dr. Celso Gomez-Sanchez graciously provided the antibody and The nonspecific binding without antibody was 2.5%, nearly identical to the nonspecific binding when excess 19-nor-DOC was added (800 pg, 2.3%; 2000 pg, 2.4%; 4000 pg, 2.2%; 10,000 pg, 2.2%). The specificity of the 19-nor-DOC antibody for other corticosteroids is shown in Table 2.…”
Section: Methodsmentioning
confidence: 81%
“…The biological significance of 19-nor-DOC was elucidated by the studies of Gomez-Sanchez et al 3 in rat adrenal regeneration hypertension. As 19-nor-DOC is a potent mineralocorticoid produced by both humans and rats, 4 -7 it would be of considerable interest to define the production and metabolism of this hormone in normal and hypertensive subjects.…”
mentioning
confidence: 99%
“…The areas corresponding to DOC and 19-nor-DOC were used for radioimmunoassay determinations using relatively specific antibodies previously described. 10 ' l3 The average recovery of (1,2 3 H) DOC and (1,2 3 H) 19-nor-DOC from the whole procedure was 53% ± 4% and 50.7% ± 4.9% respectively. Intraassay variability was 9.8% and 10%, and interassay variability was 19% and 16.6%, for DOC and 19-nor-DOC respectively.…”
Section: Assay Methodsmentioning
confidence: 93%
“…We have identified a powerful mineralocorticoid, 19-nor-deoxycorticosterone (19-nor-DOC), in the urine of rats with ARH 10 and have recently developed a method to measure the urinary excretion of 19-nor-DOC in rats. We are reporting our results of the measurements of free 19-nor-DOC and DOC in the urine and 19-nor-DOC in the serum of rats with adrenal regeneration hypertension.…”
Section: Hypertension • Mineralocorticoidsmentioning
confidence: 99%